PEMANFAATAN SMS UNTUK MENINGKATKAN PELAYANAN PENDAFTARAN PASIEN PADA RUMAH SAKIT PERMATA IBU - Sri Mulyati (Universitas Budi Luhur, 2012)
Technology is a medium that can be used to process and solve a problem more efficiently. With the increasing variety and complex of today’s human need, prove that technology is necessary for human life. One media that is currently widely used and very popular is the mobile phones that can meet the communication needs of the community at large. There are many application of mobile phones that are offered to users, and one of the most widely used by cell phone users is SMS (Short Message Service. There are many SMS technology that are widely used in implementing many application, based on SMS such as : Marquis, Polling or business application. Therefore, the SMS technology can also help the problem of “Permata Ibu”General hospital in addressing registration services. Register via SMS allows patients prior to treatment without having to come to hospital. Patients can easily search for information in advance through the menus that are available before registration. By implementing a sistem of SMS-based patient registration information to the hospital, a doctor, can find out how many patients already enrolled on a specific date and time. In addition the hospital can easily perform the latest promo. Keyword : SMS Gateway, Registration, Hospital